Volkszählung // Ich will deine Daten - Mann mit stechenden Augen
soziale Fragen;Bevölkerung;Demographie;Bevölkerungsstatistik;Volkszählung politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Widerstand